Low-temperature solution-processed flexible organic solar cells with PFN/AgNWs cathode. (September 2015) - Seo, Ji Hoon; Um, Han-Don; Shukla, Atul; Hwang, Inchan; Park, Juyun; Kang, Yong-Cheol; Kim, Chang Su; Song, Myungkwan; Seo, Kwanyong
Abstract: We report on highly efficient flexible inverted organic solar cells (IOSCs) fabricated by low-temperature solution process on polyethylene terephthalate (PET) substrate. In general, IOSCs have been required to use an annealed (>200 °C) zinc oxide (ZnO) as an electron transport layer. However, any twisting of the flexible substrate during heat treatment leads to poor device performance. To overcome this issue, we developed a novel low temperature process for flexible IOSCs using an alcohol-/water-soluble conjugated polymer, namely poly [(9, 9-bis(3′-(N, N-dimethylamino) propyl)-2, 7-fluorene)-alt-2, 7-(9, 9–dioctylfluorene)] (PFN) instead of the ZnO. Using this low-temperature process, we successfully demonstrate highly efficient flexible IOSCs that are proven to be capable of the power conversion efficiency (PCE) of 6.17% which retain 96% of its efficiency at a bending radius of R ≈5 mm or less. To the best of our knowledge, this PCE 6.17% is the best result among the reported values so far for flexible OSCs fabricated on PET substrate. Graphical abstract: Highlights: Low-temperature process adopted for application of flexible inverted organic solar cells (IOSCs). Flexible IOSCs with an ultra-thin PFN layer showed a best performance of 6.17%. The efficiency of IOSCs retains 96% of its initial efficiency at a critical bending radius.